MENGGALI ULANG MAKNA MISI ALLAH DALAM BUDAYA DIGITAL MASA KINI - Hengkeng, Putri Jenifer; Montjai, Dwi Novika; Weleng, Erika Nandini; Sabari, Felice De Giardini (DELAHA: Journal of Theological Sciences, 2025)
This article reexamines the meaning of God's mission in digital culture. Its aim is to formulate a new understanding of mission that is relevant in the digital age, where technology is transforming how people interact and practice religion. This qualitative research utilizes literature studies and data from various sources, including observation. The results indicate that digitalization opens up opportunities for the church through instant connectivity, active participation, and user-generated content. However, challenges such as information overload and superficial spirituality also arise. The church must adapt, transforming its mission through the digitalization of evangelism, diakonia, koinonia, and martyria, as well as improving digital literacy and digital theology to maintain the integrity of faith. In conclusion, the church must leverage the digital space as a new, adaptive, and inclusive mission field, grounded in the teachings of Jesus Christ. .